(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Background: Fall from a height is one of the major causes of blunt-force trauma and it is also the most common type of accident in occupational settings. Builders, electricians, miners, painters, psychiatrists and pediatrics are particularly at risk. Method: A retrospective study was done in the Department of Forensic Medicine of BPS GMC (W), Khanpur Kalan, Sonipat, Haryana from 1 January 2017 to 31 December 2022. A comparative analysis of various factors such as gender, age groups, height of falls and injury patterns was done. Results: A total of 55 patients with fall-related injuries were identified during these 5 years of study. In all, 46 were male (83.6%) and 09 were female (16.4%). Head and neck (72.7%) and thorax (69.1%) are maximum affected region followed by the abdomen (45.5%), limbs (30.1%) and spines (9.1%). Majority of injured individuals (40%) belongs to working age group, that is, 21– 30 years. Conclusion: It was observed that mortality from height is mainly accidental and thus preventable. Variations in the pattern of injuries by age, gender and height of fall provide important information for targeted preventive measures.